Kuduri’nin ecrid adlı eserinde hanefiler ve iafiilerin nasslara dayalı ihtilafları : Kitabü’n-nikah çerçevesinde - Ünver, Ahmet Numan (My University, 2013)
Hicrî IV. asır âlimlerinden olan ve Irak’ta Hanefî mezhebinin riyasetine yükselen olan Kudûrî, kolay ve akıcı bir dile sahip olan eseri Tecrîd’de, Hanefî ve Şâfiî mezhepleri arasındaki ihtilâflı meseleleri müdellel bir şekilde ele almış, Şâfiî mezhebine olan vukufiyetini ortaya koymuştur. Delillerinin kritiğini yapmış, nassları farklı açılardan değerlendirmiş, konularla ilgili görüşleri açıklarken farklı yöntemlere de başvurmuş; böylece mezhepler arası ihtilâfların neden ve nasıl ortaya çıktığına dair önemli mülahazalar sunmuştur. Kitâbü’n-nikâh bahsinde nasslara dayalı ihtilâflar, sübûta ve delâlete dair olmak üzere temelde ikili bir taksime tabi tutulmuştur. Rivayet malzemesi hakkındaki sübûta dair ihtilâflar, rivayetlerin senedinin ittisaline ve aktarılan sözlerin kime ait olduğuna yöneliktir. Delâlete dair ihtilâflar ise beşli bir taksimata sahiptir. Buna göre nasslarda yer alan lafızların vaz’ına, manaya mefhum ve delâletine, teviline, kapsamına ve gramatik açıdan farklı yorumlanmasına dair ihtilâflar, nassların delâletiyle ilgili ihtilâfların temelini oluşturmaktadır. Eserde bunların her birinde cedel metodu kullanılarak delillerin münakaşası yapılmakta ve Hanefî mezhebinin görüşleri savunulmaktadır.

al-Qudūrī, a prominent Ḥanafī scholar of 4th century of the Hijra, who then managed to become the chief scholar of the maḏhab in ʿIrāq, discusses the controversial issues between the Ḥanafī and the Šāfiʿī Schools along with their evidences in his work al-Tajrīd, thus proving his authority in Šāfiʿī School. In al-Tajrīd, with a smooth and easy language, he criticizes the evidences of the above-mentioned schools, evaluates the nuṣūṣ in different aspects, and he also uses different methods in explaining the opinions on a certain topic, thus providing valuable insights into the reasons why and how the different Islamic law schools came into being. In Kitāb al-Nikāḥ, al-Qudūrī classifies the controversies originating from the nuṣūṣ into two main sections; those related to subūt and those related to dalāla. The former regarding the material of riwāya is about the continuation of the chain of riwāya and about that to whom the transmitted words belong. As to the latter, he divides it into five subdivisions. According to this division, controversies on the waḍʿ of words in the nuṣūṣ, the meaning, the mafhūm and the dalāla, interpretation, and extent and different grammatical interpretation of the nuṣūṣ constitute the basics of the controversies related to dalāla of the nuṣūṣ. He employs the jadal method in each section in order to evaluate the evidences of the schools and at the end, he favors the opinions of the Ḥanafī School over the opinions of other schools.
Keywords: Fıkıh; İslam Hukuku